Intervention of Progressive Muscle Relaxation on Anxiety and Sleep Quality in COVID-19 Patients : A Systematic Review - Nurul Imam; Alfian Bayu Indrawan; Rofi Syahrizal; Shafaat Pranata (Poltekkes Kemenkes Palu, 2022)
COVID-19 is an infectious disease. COVID-19 patients will experience anxiety, thus disturbing the patient's sleep quality. Pharmacological therapy given in the long term poses a risk to the health of the body. This study aims to determine the effectiveness of progressive muscle relaxation in COVID-19 patients to reduce anxiety and improve sleep quality. The studies were identified systematic by searching the database with the keywords “COVID-19 AND Anxiety AND Sleep Quality AND progressive Muscle Relaxation.” The results consist of Web of Science 3 articles, Scopus 3 articles, Science Direct 135 and Pro Quest 501 articles. Eligible articles were selected according to the inclusion and exclusion criteria, COVID-19 patients with anxiety and sleep disturbances as well as with PMR intervention and articles published in English based on the last 3 years study. In assessing the bias and methodological quality of this study using the Joanna Briggs Institute (JBI) critical appraisal checklist tool. From 642 references, after a selection there were 5 references describing in detail progressive muscle relaxation exercises that could be used together with pharmacological during treatment in isolation rooms. Progressive muscle relaxation exercises are performed 2 times a day, in the morning and before going to bed, with a duration of 20-30 minutes. Progressive muscle relaxation significant reduces anxiety and improves sleep quality in COVID-19 patients during isolation treatment.